Implementasi Program Gita Suara Snepata Dalam Mengembangkan Karakter Pada Siswa di SD No.4 Benoa Kabupaten Badung - Ni Wayan Sugi Jutari (JAPAM (Jurnal Pendidikan Agama), 2025)
The development of increasingly advanced technology and communication has caused significant changes in human behavior. Changes in the level of human behavior are often called moral degradation. Moral degradation is a moral decline in humans. In overcoming the occurrence of moral degradation,one of the ways that is done is by preserving cultureThis cultural preservation is very important to do seeing that in today's era, the interest of the younger generation in mekidung is decreasing. The decline in interest in mekidung and the decline in character were also experienced by students at SD No.4 Benoa. Based on these problems, Hindu teachers formed a program called the Gita Suara Snepata Program. The formation of this program has the purpose of preserving the existence of dharmagita and instilling character values among students at the elementary school level. The implementation of the Gita Suara Snepata Program can be divided into 3 stages, namely: planning, implementation, and evaluation. The implementation of the Gita Suara Snepata Program at SD No.4 Benoa experienced several obstacles, such as the difficulty of increasing student motivation, conditions or situations that are not supportive, the influence of technology, and the influence of western culture. Therefore, efforts are needed to anticipate the obstacles of the Gita Suara Snepata program, namely by implementing strategies that are attractive to students, preparing special rooms for students, utilizing technology and instilling cultural love in students.